Insights into mesoporous nitrogen-rich carbon induced synergy for the selective synthesis of ethanol. (30th October 2020) - Das, Subhasis; Sengupta, Manideepa; Lippi, Renata; Patel, Jim; Bag, Arijit; Nayak, Chandrani; Jha, Shambhu Nath; Bordoloi, Ankur
Abstract: This work provides an in-depth study on selective ethanol synthesis over cobalt and copper supported on mesoporous nitrogen-rich carbon (MCN) materials. A series of nano-sized Cu–Co@MCN catalysts with variable compositions were designed to maximize the ethanol yield from bio-derived syngas (CO/H2  > 2) by utilizing a nitrogen-rich mesoporous carbon (MCN), which serves two purposes i) the stabilisation of relatively small sized Co nanoparticle crystallites (Co: below 10 nm, geometrical structural promoter) with strong metal support interactions and ii) the promotion of sufficient electronic interactions (electronic promoter) to improve the reducibility of the catalyst. Characterisation of these novel catalysts by a range of techniques (XRD, BET, TPR, HRTEM, XPS, and EXAFS) confirmed that the metal ions are confined within the MCN matrix with highly uniform dispersion. This enhances metal support interactions, which promotes associative CO adsorption over complete CO dissociation. The Cu–Co@MCN catalyst shows potential for higher alcohol synthesis with high product selectivity for C1–C3 oxygenates in the liquid product stream, making it an attractive solution to alternative synthesis of higher alcohols. To elucidate the actual role of surface support nitrogen in-situ synchrotron PXRD studies were performed on the catalyst systems as well as on traditional support alternatives, e.g., carbon nanotubes and activated carbon. Furthermore, insights on catalyst deactivation and selectivity were achieved by in-situ high temperature infrared spectroscopic analysis (DRIFTS) studies, which is followed by in-depth Density Functional Theory (DFT) calculations outline the plausible route via stabilisation of CHO∗, CH2 O∗ intermediates for selective ethanol formation. Graphical abstract: Image 1